2003
DOI: 10.1046/j.1468-2982.2003.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in the Treatment of Chronic Migraine

Abstract: The purpose of this study was to evaluate the efficacy of topiramate in the treatment of chronic migraine. This was a double-blind, randomized, placebo controlled, parallel-group study. Patients suffering from chronic migraine with analgesic overuse were randomly assigned in a 1 : 1 ratio to receive topiramate or placebo. Following a baseline phase of eight weeks, the study drug was titrated in 25-mg increments over one week to 50 mg daily. Titration phase was followed by a 8-week maintenance phase. Number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
111
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 22 publications
5
111
0
6
Order By: Relevance
“…These chronic migraine patients have been shown to respond satisfactorily to topiramate [7,8], even in the presence of overuse and in controlled conditions [9,10]. Interestingly, among the group of responders in long-term treatment there was only one patient whose headaches became worse while on topiramate.…”
Section: Discussionmentioning
confidence: 99%
“…These chronic migraine patients have been shown to respond satisfactorily to topiramate [7,8], even in the presence of overuse and in controlled conditions [9,10]. Interestingly, among the group of responders in long-term treatment there was only one patient whose headaches became worse while on topiramate.…”
Section: Discussionmentioning
confidence: 99%
“…Silvestrini et al [7] showed the efficacy of topiramate in chronic migraine with analgesic overuse preventive treatment. Only 28 patients were studied receiving topiramate in a lower dose (50 mg).…”
Section: Discussionmentioning
confidence: 99%
“…The encouraging results from a small randomized, placebo-controlled trial (RCT) of topiramate (50 mg daily) in 28 patients with CM and medication overuse paved the way for larger studies [58]. Two multicentre, parallel-group RCT in Europe (59 patients) and the USA (328 patients) showed that topiramate at a daily dose of 100 mg during 16 weeks was effective as a preventive therapy for CM [59,60].…”
Section: Topiramatementioning
confidence: 99%